2017
DOI: 10.1136/bjsports-2016-097270.105
|View full text |Cite
|
Sign up to set email alerts
|

Measuring cognitive-motor integration to detect prolonged performance declines post-concussion

Abstract: ObjectiveThere is a higher risk of re-injury for athletes with concussion history when returning to play, despite being asymptomatic and cleared for activity. One possible explanation is that current return to play assessments test thinking and moving separately, but sport activities often require their concurrent processing (cognitive-motor integration, CMI). The aim of this research is to characterize CMI performance across a range of ages and skill levels following concussion. We hypothesize that there will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This idea is in line with findings of previous concussion history studies of youths, varsity athletes, and elite athletes. There was an inverse relationship between CMI deficits and skill level across these studies (Brown et al., 2015; Dalecki et al., 2016; Hurtubise, 2016; Sergio et al., 2017). All of these results strongly suggest an important role of visuomotor sport‐related experience in compensation for CMI deficits post‐concussion.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This idea is in line with findings of previous concussion history studies of youths, varsity athletes, and elite athletes. There was an inverse relationship between CMI deficits and skill level across these studies (Brown et al., 2015; Dalecki et al., 2016; Hurtubise, 2016; Sergio et al., 2017). All of these results strongly suggest an important role of visuomotor sport‐related experience in compensation for CMI deficits post‐concussion.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies showed that post‐concussive CMI deficits had an inverse relationship with age and skill level (Brown, Dalecki, Hughes, Macpherson, & Sergio, 2015; Dalecki et al., 2016; Hurtubise, 2016; Sergio et al., 2017). Thus, one might expect that more years of eye–limb coordination‐related sports experience could compensate for CMI skill impairment.…”
Section: Introductionmentioning
confidence: 96%
“…In the present study, we expand on these findings with details about the time course of EHD deficits in youth with concussion history to include task demand. Eye-hand decoupling is an important and common skill on the sport-field, in particular, in popular contact sports such as American football, lacrosse or hockey [23].…”
Section: Discussionmentioning
confidence: 99%